2015
DOI: 10.4049/jimmunol.1500174
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Induced Tolerance Depends on Peripheral Regulatory T Cells That Require Hopx To Inhibit Intrinsic IL-2 Expression

Abstract: Dendritic Cells (DCs) can induce peripheral immune tolerance that prevents autoimmune responses. Antigen presentation by peripheral DCs under steady state conditions leads to a conversion of some peripheral CD4+ T cells into Treg cells that require Homeodomain Only Protein (Hopx) to mediate T cell unresponsiveness. However, the roles of these peripheral (p)Treg cells in averting autoimmune responses as well as immunological mechanisms of Hopx remain unknown. Here we report that Hopx+ pTreg cells converted by D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 73 publications
(84 reference statements)
7
62
0
Order By: Relevance
“…Other studies found a similar extrathymic conversion by specialized CD103 + DCs presenting intestinal and food antigens within gut associated lymphoid tissues (GALT) of Foxp3 + Treg cells contributing to maintenance of local immune homeostasis [27, 28, 7073]. Recent results of experiments in an EAE model using Hopx −/− mice that have specific deficiencies in functions and survival of pTreg cells (but not tTreg cells) helped to further establish the essential roles of pTreg cells in the maintenance of DC-induced tolerance and prevention of organ-specific autoimmunity [54, 74]. Overall, these results suggested that specialized tolerogenic DCs in steady state are not immature bystanders but rather inducers of active processes in T cells to promote mechanisms of peripheral tolerance including a conversion of pTreg cells.…”
Section: Exploring Tolerogenic Mechanisms Of Peripheral Dcs In Vivomentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies found a similar extrathymic conversion by specialized CD103 + DCs presenting intestinal and food antigens within gut associated lymphoid tissues (GALT) of Foxp3 + Treg cells contributing to maintenance of local immune homeostasis [27, 28, 7073]. Recent results of experiments in an EAE model using Hopx −/− mice that have specific deficiencies in functions and survival of pTreg cells (but not tTreg cells) helped to further establish the essential roles of pTreg cells in the maintenance of DC-induced tolerance and prevention of organ-specific autoimmunity [54, 74]. Overall, these results suggested that specialized tolerogenic DCs in steady state are not immature bystanders but rather inducers of active processes in T cells to promote mechanisms of peripheral tolerance including a conversion of pTreg cells.…”
Section: Exploring Tolerogenic Mechanisms Of Peripheral Dcs In Vivomentioning
confidence: 99%
“…Consistent with such actively induced mechanisms, various immune mediators and environmental signals including materials from dead cells and some microbial products may enhance tolerogenic properties of DCs as reviewed by Manicassamy and Pulendran in [75], Sancho and Reis e Sousa in [76] and Mellman in [37]. The specific tolerogenic mechanisms of such tolerogenic types of DCs and the roles of pTreg cells have become an area of intense investigation [37, 54, 68, 70, 71, 73, 77, 78]. …”
Section: Exploring Tolerogenic Mechanisms Of Peripheral Dcs In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…There is scant prior evidence of a role for these genes in pulmonary or immune function, lung disease, or asthma, although HOPX is involved in the function of regulatory T cells [52].…”
Section: Discussionmentioning
confidence: 99%